Membangun Kemandirian Perilaku Personal Hygiene Pada Lansia Di Panti Jompo Welas Asih Tasikmalaya - Aneng Yuningsih (Yayasan Inspirasi El Burhani, 2023)
Introduction: The increase in the number of elderly will affect various aspects of elderly life, especially the health and welfare of the elderly. One effort to improve and maintain the health of the elderly is by maintaining personal hygiene. The need for personal hygiene must be a top priority for the elderly because good personal hygiene means that the elderly have a low risk of experiencing infectious diseases of the eyes and ears. Objective: Increase the knowledge and independence of elderly people in meeting basic personal hygiene needs with the number of activity participants totaling 24 elderly people in the active elderly category. Method: Implementation of community service is carried out through stages: Preparation, Socialization, Implementation of Activities (Explanation of material, Simulation and Evaluation) and Closing. Results: Based on the results of calculating the pre-test and post-test scores for providing education and simulation, data showed that there was a significant increase in the knowledge of the elderly, from an average pre-test score of 35 to 85. The average post-test score had increased in results. post-test was 50, with the highest score on the post-test being 90 (14 people). Conclusion: Based on the results of the evaluation of Community Service activities, the picture of understanding about efforts to increase independence and awareness of personal hygiene in the elderly through education and simulation after being provided with education has increased significantly.